Early Changes in Costameric and Mitochondrial Protein Expression with Unloading Are Muscle Specific. (16th September 2014) - Flück, Martin; Li, Ruowei; Valdivieso, Paola; Linnehan, Richard M.; Castells, Josiane; Tesch, Per; Gustafsson, Thomas
Abstract : We hypothesised that load-sensitive expression of costameric proteins, which hold the sarcomere in place and position the mitochondria, contributes to the early adaptations of antigravity muscle to unloading and would depend on muscle fibre composition and chymotrypsin activity of the proteasome. Biopsies were obtained from vastus lateralis (VL) and soleus (SOL) muscles of eight men before and after 3 days of unilateral lower limb suspension (ULLS) and subjected to fibre typing and measures for costameric (FAK and FRNK), mitochondrial (NDUFA9, SDHA, UQCRC1, UCP3, and ATP5A1), and MHCI protein and RNA content. Mean cross-sectional area (MCSA) of types I and II muscle fibres in VL and type I fibres in SOL demonstrated a trend for a reduction after ULLS (0.05 ≤ P < 0.10 ). FAK phosphorylation at tyrosine 397 showed a 20% reduction in VL muscle (P = 0.029 ). SOL muscle demonstrated a specific reduction in UCP3 content (- 23 %; P   =   0.012 ). Muscle-specific effects of ULLS were identified for linear relationships between measured proteins, chymotrypsin activity and fibre MCSA. The molecular modifications in costamere turnover and energy homoeostasis identify that aspects of atrophy and fibre transformation are detectable at the protein level in weight-bearing muscles within 3 days of unloading.